Depth and lateral deviations in guided implant surgery: an RCT comparing guided surgery with mental navigation or the use of a pilot‐drill template. Issue 11 (2nd September 2014) - Vercruyssen, M.; Coucke, W.; Naert, I.; Jacobs, R.; Teughels, W.; Quirynen, M.
Abstract Aim To assess the accuracy of guided surgery compared with mental navigation or the use of a pilot‐drill template in fully edentulous patients. Material and methods Sixty consecutive patients (72 jaws), requiring four to six implants (maxilla or mandible), were randomly assigned to one of the following treatment modalities: Materialise Universal® mucosa, Materialise Universal® bone, Facilitate™ mucosa, Facilitate™ bone, mental navigation, or a pilot‐drill template. Accuracy was assessed by matching the planning CT with a postoperative CBCT. Deviations were registered in a vertical (depth) and horizontal (lateral) plane. The latter further subdivided into BL (bucco‐lingual) and MD (mesio‐distal) deviations. Results The overall mean vertical deviation for the guided surgery groups was 0.9 mm ± 0.8 (range: 0.0–3.7) and 0.9 mm ± 0.6 (range: 0.0–2.9) in a horizontal direction. For the non‐guided groups, this was 1.7 mm ± 1.3 (range: 0.0–6.4) and 2.1 mm ± 1.4 (range 0.0–8.5), respectively (P < 0.05). The overall mean deviation for the guided surgery groups in MD direction was 0.6 mm ± 0.5 (range: 0.0–2.5) and 0.5 mm ± 0.5 (range: 0.0–2.9) in BL direction. For the non‐guided groups, this was 1.8 mm ± 1.4 (range: 0.0–8.3) and 0.7 mm ± 0.6 (range 0.0–2.9), respectively. The deviation in MD direction was significantly higher in the non‐guided groups (P = 0.0002). Conclusion The most important inaccuracy with guided surgery is in vertical direction (depth). The inaccuracy in MD or BL direction is clearly less. For non‐guided surgery, the inaccuracy is significantly higher.